(untitled) (Global Journal of Human-Social Science, 2019)
Syair Burdah Melayu is a form of oral tradition that currently sustainable. Syair Burdah Melayu was created because immigrant community culture acculturation occur in Loloan, Bali. The fusion of the immigrant culture forming the absurdity in syair Burdah Melayu structure. This study aims to describe the meaning and form of syair Burdah Melayu with socio-cultural impact. Problem analysis are the meaning and variance form in syair Burdah Melayu. Theory used are dynamic structuralism by Mukarovsky and Felik Vodicka combined with semiotic theory by Charles Sander Pierce to explain the meaning and form of syair Burda Melayu that influence by socio-culture of Loloan Barat community. The research method uses qualitative types by using words to describe poetry analysis results. From the results of the analysis it’s known that the form of Syair Burdah Melayu is influenced by other cultural elements such as Arab, Javanese, and Malay so the form of the Syair like separate but actually a whole unit.